Experiencing Exclusion among Dalits: A Sociological Study of Bauris and Hadis - K. M. ZIYAUDDIN (IJRDO - Journal of Social Science and Humanities Research, 2017)
This study is primarily based on intensive fieldwork. The focus of the paper is to seek an understanding about the perceptions of Dalits namely Bauris and Hadis. They are not very active in terms of participation and responding to the problems of health and illness. Collecting information on experiences of illnesses needs very close interaction with the people (Banerjee, 1980). Sociologists often perceive that Illness as something experienced, represented, negotiated by individuals which is reflected in the narratives and in-depth interviews of people. Perception on illness and health invariably depends on the socio-cultural conditions of the people. In this context, it becomes essential to understand the socio-cultural milieu of SCs in the field. The various and myriad form of expression about illness exist not only from one individual to another but also from one group to another. Therefore a close interaction with the group undertaken and elaborated in this study paper to understand the socio-cultural, economic as well as health perceptive.